Anesthesia management of ophthalmic surgery for patient with suspected/confirmed COVID-19 -Saudi Anesthesia Society guidelines- - Nauman Ahmad; Abdul Zahoor; Abdulaziz E Ahmad; Abdelazeem El Dawlatly (Saudi Journal of Anaesthesia, 2020)
The outbreak of the novel coronavirus (COVID-19) has been declared a global pandemic. With a mortality rate reaching up to 5%, healthcare professionals treating patients with COVID-19 are at a significantly higher risk for exposure themselves. Given the rapidly progressing rate of COVID-19, there is an urgent need for developing guidelines within each specialty. This article discusses guidelines specifically for anesthesiologists dealing with ophthalmic surgeries with suspected or confirmed COVID-19 patients. Anesthesiologists always work in the proximity of the patient's face while performing either ocular regional anesthesia or while managing the airway in the process of intubation/extubation. Within these guidelines, the emphasis is provided on thorough preoperative screening to identify COVID-19 patients and to prevent the exposure of healthcare staff by following standard personal protective equipment (PPE) precautions.